2012
DOI: 10.1542/peds.2011-0012
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Battery-Related Emergency Department Visits in the United States, 1990–2009

Abstract: This study evaluated battery-related ED visits among US children using a nationally representative sample. Batteries pose an important hazard to children, especially those ≤ 5 years of age. The increasing number and rate of battery-related ED visits among children underscore the need for increased prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 21 publications
(41 reference statements)
2
63
0
3
Order By: Relevance
“…[10] This low incidence has increased, however, with the widespread use of button batteries in the household. [11][12][13] Button batteries range in size from 6 to 25 mm in diameter. Batteries larger than 12 mm are more likely to become lodged in the esophagus of young children.…”
Section: Discussionmentioning
confidence: 99%
“…[10] This low incidence has increased, however, with the widespread use of button batteries in the household. [11][12][13] Button batteries range in size from 6 to 25 mm in diameter. Batteries larger than 12 mm are more likely to become lodged in the esophagus of young children.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Several studies have indicated that most children who ingested batteries were ≤ 6 years of age. [2,6,7,8] The National Capital Poison Center reported a total of 39 fatal cases of button battery ingestion in the USA from 1977-2014. [9] Reasons proposed for this dramatic increase are that there is an increase in production of larger, more powerful button batteries and more battery-powered electronic devices are being used by children.…”
Section: Discussionmentioning
confidence: 99%
“…около 3300 обращений по поводу удаления инородных тел -батареек у детей в возрасте до 18 лет, в том числе у 10,2% батарейки удаляют из полости носа (0,29 случаев на 100 000 детей) [5]. В настоящее время батарейки составляют 2% от числа всех неорганических инородных тел [1].…”
Section: ключевые слова: инородное тело носа дисковая батарейка детunclassified